Breast Self-examination and its Effective Factors Based on the Theory of Planned Behavior among Women in Kerman, Iran - Esmat Rezabeigi-davarani; Narges Khanjani; Mostafa Falahi; Salman Daneshi; Abedin Iranpour (Hamadan University of Medical Sciences, 2016)
Background and Objectives: Breast cancer is the most common form of malignant diseases in women. Early diagnosis is effective on its successful treatment. The aim of this study was to evaluate breast self-examination and its effective factors based on the theory of planned behavior among women in Kerman, Iran. Materials and Methods: In this descriptive-analytical cross-sectional study, 300 women referred to the health centers in Kerman, Iran, were selected by the cluster and convenience sampling. Data were collected using questionnaires included demographic variables and questions about knowledge and constructs of the theory of planned behavior. Data analysis was done using descriptive statistics and Pearson's correlation, Spearman, Chi-square, independent t-test, Mann-Whitney and logistic regression with the SPSS 21 software. Results: The mean age of the participants was 30.26 ± 8.18 years. Results showed that 12.7% of the women performed breast self-examination regularly every month. The most common reason for not doing breast self-examination was not knowing how to perform it. Knowledge was the most important predictor in breast self-examination (OR= 0.896, P <0.001). There was a significant difference in the average scores of knowledge, attitude, perceived behavioral control and behavioral intention between groups that did and did not perform breast self-examination (P <0.05). Conclusions: Education interventions based on the theory of planned behavior can be implemented for increasing women's knowledge and empowering them in timely diagnosis and treatment of breast cancer.